Analysis of Students' Mathematical Problem-Solving Ability in Terms of Gender Differences - Sholihah, Imroatus; Chandra, Tjang Daniel; Anita, Yuli (International Journal of Insights for Mathematics Teaching, 2023)
This research illustrates students' ability to solve mathematical problems by considering gender differences. This type of research is descriptive qualitative. This research topic is about systems of linear equations with 2 variables. The subjects of this research were 24 students in class VIII of SMP Negeri 3 Malang for the 2023/2024 academic year. The step in collecting research data information is a test. The data analysis technique involves categorizing the level of mathematical problem-solving ability into high, medium problem-solving ability into high, medium, and low. Research findings show that the average score for male students is 89.49, while the average score for female students is 94.47. Based on research findings, it can be concluded that female students' ability to solve mathematical problems is better than male students.